PENGARUH DUKUNGAN SOSIAL TERHADAP PENYESUAIAN DIRI SANTRI KELAS 7 DI SMP ISLAM EXCELLENT AS SYAFI’AH NGANJUK - Umma Ainun Zahro (SHINE: JURNAL BIMBINGAN DAN KONSELING, 2024)
Students who have just entered the Islamic boarding school must be able to adapt themselves. They must participate in all activities that exist at the Islamic boarding school, both formal and non-formal. Besides that, students must adapt well, so social support is needed from people around the students, but the social support given to students is not always optimal, this causes students to have difficulty adjusting themselves. The purpose of this study was to determine the effect of social support on the adjustment of new students in grade 7 at the SMP Islam Excellent As Syafi’ah Nganjuk. This study uses a quantitative with a correlational type that is measured using two scales, namely social support and self-adjustment. The subjects in this study were new students in grade 7 Islamic Middle School Excellent As Syafi'ah Nganjuk. totaling 158 students. The results in this study indicate that there is an influence of social support on self-adjustment. Social support has a significant effect on adjustment with a sig value of <0.05 (0.000 <0.05) and social support affects adjustment with a percentage value of 32.1%.